KAJIAN SUMBER ENERGI PADA PENGOLAHAN KELAPA SAWIT MENJADI CRUDE PALM OIL (CPO) DI PT. ALNO AGRO UTAMA SUMINDO OIL MILL, BENGKULU UTARA - Lukman Hidayat; Fitri Electrika Dewi Surawan; Arga Harianda Lumban Raja (AGROINTEK, 2017)
Increasing demand for Crude Palm Oil (CPO) as the vegetable oil was causing the industry to cultivate palm oil increased, so that the energy required to produce CPO also increased. The purpose of this study is to identify the type, source and calculate the amount of energy needs, calculate the level of efficiency and energy savings opportunities. Stages of the research are  initial energy analysis, a detailed energy, and energy analysis in processing systems. Based on the research results, to produce each kg of CPO processing capacity of 60 ton TBS / hour with a recovery rate of 20.59% of primary energy needs of 16.200679 MJ / kg. Real boiler efficiency of 45.69%, the real efficiency of the turbine was 94, 86%. Turbine efficiency  to generate electrical energy by 1.09%, the technical efficiency of 66.80% turbines, diesel generators technical efficiency of 47.25%, the technical efficiency of electric motors by 59.37%.  The total efficiency  of  electricity  use by 4,75%, the efficiency of diesel estate of 1.379% and the efficiency of the use of steam at 93.77%. Energy can be saved by 0.0442 MJ / kg with a description of human powered energy of 0.0004316 MJ / kg, energy electrical energy by .04372 MJ / kg. While energy can be stored on the excess energy to fuel biomass boiler was 1.45 MJ / kg